2023
DOI: 10.3390/molecules28176373
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Biomaterials Trigger Remineralization and Antimicrobial Effects for Dental Caries Restoration

Yuexiao Li,
Minda Liu,
Mingyu Xue
et al.

Abstract: Dental caries is the most prevalent chronic disease globally, significantly impacting individuals’ quality of life. A key reason behind the failure of implanted restorations is their biological inactivity, meaning they are unable to form crosslinks with the surrounding tooth structures, thus making patients susceptible to implant loss and recurrent tooth decay. For the treatment of caries, antibacterial medicine and remineralization are effective means of treating the recurrence of caries. Owing to the rapid p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 103 publications
(115 reference statements)
0
1
0
Order By: Relevance
“…The studies evaluating chemical content included elements commonly found in dentin tissues, such as Ca, P, and Ca/P, which in case of loss would be compatible with demineralization (32). EDX microanalysis was complementary to the morphological analysis by SEM in the studies analyzed.…”
Section: Primary Outcomesmentioning
confidence: 99%
“…The studies evaluating chemical content included elements commonly found in dentin tissues, such as Ca, P, and Ca/P, which in case of loss would be compatible with demineralization (32). EDX microanalysis was complementary to the morphological analysis by SEM in the studies analyzed.…”
Section: Primary Outcomesmentioning
confidence: 99%